Application of Swedish Massage Therapy on Reducing Blood Pressure in Elderly with Hypertension at BPSTW Budi Luhur: A Nursing Case Study - Nur Fatimah, Tri; Indah Yulitasari, Brune (CV. Literasi Publikasi Indonesia, 2026)
Hypertension is a common cardiovascular disease in the elderly and is known as a